Appropriate particle size of rice straw promoted rumen fermentation and regulated bacterial microbiota in a rumen simulation technique system - Li, Zhiqing; Qiu, Huijing; Lan, Xinyi; Wang, Zuo; Shen, Weijun; Wan, Fachun; Xiao, Dingfu; He, Jianhua (Frontiers in Veterinary Science, 2023)
The purpose of this study is to reveal the effects of different particle sizes of rice straw on the rumen protozoa count, nutrient disappearance rate, rumen fermentation, and microbial community in a rumen simulation technique (RUSITEC) system. In this experiment, a single-factor random trial design was adopted. According to the different particle sizes of rice straw, there were 3 treatments with 3 repeats in each treatment. According to the NRC (2012) standard, three kinds of goat TMR, with the same nutrients were used to carry out a 10 days in vitro fermentation experiment using the rumen simulation system developed by Hunan Agricultural University, including 6 days the pretrial period and 4 days formal period. This study found that the organic matter disappearance rate, concentrations of total volatile fatty acids (VFAs), acetate, propionate, and iso-butyrate were greatest in the 4 mm group (p < 0.05). There were no significant differences in the alpha diversity, among the three groups (p > 0.05). The relative abundance of Treponema and Ruminococcus of the 2mm group increased; The relative abundance of Butyrivibrio and Prevotella in samples increased in the 4mm group. In addition, the results of correlation analysis showed that Prevotella and Ruminococcus was positively correlated with butyrate, ammonia-N, dOM and d ADF (p < 0.05) and negatively correlated with valerate (p < 0.05); Oscillospira was positively correlated with valerate (p < 0.01) and negatively correlated with propionate, butyrate, ammonia-N, dOM and dADF (p < 0.05). The present results imply that compared to the other groups, rice straw particle size of 4 mm may improve the disappearance rate of nutrients and promote the production of volatile fatty acids by regulating ruminal microorganisms.